2022
DOI: 10.3390/ijms23169049
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Retinal Pigment Epithelial Cells Derived from Induced Pluripotent Stem Cells of a Retinitis Pigmentosa Patient with the PRPF6 Mutation

Abstract: Pre-mRNA processing factors (PRPFs) are vital components of the spliceosome and are involved in the physiological process necessary for pre-mRNA splicing to mature mRNA. As an important member, PRPF6 mutation resulting in autosomal dominant retinitis pigmentosa (adRP) is not common. Recently, we reported the establishment of an induced pluripotent stem cells (iPSCs; CSUASOi004-A) model by reprogramming the peripheral blood mononuclear cells of a PRPF6-related adRP patient, which could recapitulate a consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
1
0
1
Order By: Relevance
“…In addition, ROs and RPE models from patient-specific iPSCs with the PRPF31 mutation showed impaired pre-mRNA splicing process as described by Baskin et al On the other hand, abnormal photoreceptor and RPE changes were also observed, including cell morphology, cilium structure, apical-basal polarity, and phagocytosis function of the photoreceptor outer segment (POS) [ 41 ]. Such an aberrant phenotype was also observed in iPSC-RPE cells from the PRPF6- mutated patients [ 42 ]. These reports suggested that progressive RPE and photoreceptor degeneration might be attributed to the mis-splicing of genes vital for retinal structure and function.…”
Section: Application Of Patient-derived Organoids In Irdsmentioning
confidence: 81%
“…In addition, ROs and RPE models from patient-specific iPSCs with the PRPF31 mutation showed impaired pre-mRNA splicing process as described by Baskin et al On the other hand, abnormal photoreceptor and RPE changes were also observed, including cell morphology, cilium structure, apical-basal polarity, and phagocytosis function of the photoreceptor outer segment (POS) [ 41 ]. Such an aberrant phenotype was also observed in iPSC-RPE cells from the PRPF6- mutated patients [ 42 ]. These reports suggested that progressive RPE and photoreceptor degeneration might be attributed to the mis-splicing of genes vital for retinal structure and function.…”
Section: Application Of Patient-derived Organoids In Irdsmentioning
confidence: 81%
“…Клетки сетчатки, полученные из ИПСК пациента с макулярной телеангиэктазией, демонстрировали нарушение митохондриальной функции [46]. Аномальные клетки пигментного эпителия образовывались из ИПСК пациента с пигментным ретинитом [47]. А в другом исследовании моделирование пигментного ретинита с помощью полученных из ИПСК ретиноидных органоидов показало массированную гибель клеток после их формирования [48].…”
Section: гены и клетки | Genes and Cellsunclassified